2005 IEEE International Symposium on Circuits and Systems
DOI: 10.1109/iscas.2005.1465943
|View full text |Cite
|
Sign up to set email alerts
|

Decision Feedback Equalizer With The Blind Matched Filter Estimation

Abstract: The optimal receiver front-end is the Matched Filter (MF) for a maximum Signal-to-Noise Ratio (SNR) in a communication channel with an Additive White Gaussian Noise (AWGN). The sampled MF output can be processed with the suboptimal yet computationally effective Decision Feedback Equalizer (DFE). In this paper, the filters of the DFE are derived in terms of the channel autocorrelation sequence which is estimated blindly using the sampled channel output signal. Initially, the MF followed by the DFE receiver the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In Appendix B it is shown that as J gets larger, the very last coefficient of f F increases in value, while that of early filter coefficients get smaller and reach to zero. Since the first L components would be equal to zero, the filter in (30) can also be used as an alternative to (26).…”
Section: Effect Of the Feedforward Filter Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…In Appendix B it is shown that as J gets larger, the very last coefficient of f F increases in value, while that of early filter coefficients get smaller and reach to zero. Since the first L components would be equal to zero, the filter in (30) can also be used as an alternative to (26).…”
Section: Effect Of the Feedforward Filter Lengthmentioning
confidence: 99%
“…However, once the matched filter is estimated so that the channel is, the channel estimate could be used to perform the Viterbi algorithm while the channel being updated in decision directed mode. See [26] for further reading on how the Viterbi algorithm can be used in the BMF receivers.…”
Section: All-adaptive Bmf Receiver For Fractionally Spaced Equalizationmentioning
confidence: 99%